(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
The aim of the contribution is to introduce the monographic section resulting from the conference Poteri patrimoni scritture. L’abbazia di Pomposa tra esarcato e regno (secoli IX-XI), organised as part of the scientific project ‘Cantiere Pomposa’. After outlining a brief assessment of the studies on the manuscript heritage of Pomposa, rooted in 18th century ecclesiastical erudition, the authors emphasise the importance of the change of perspective, from local to supra-local, and the focus on the allocation of fiscal assets to the royal monasteries in order to understand the political-institutional and cultural history of the important abbey of the Po delta in the central centuries of the Middle Ages.